Diagnosis of Student Misconception in Heat Material Using Tier Test - Heny Ekawati Haryono; Khafidhoh Nurul Aini; Achmad Samsudin; Parsaoran Siahaan (Jurnal Pembelajaran Fisika, 2021)
Students, basically, possess prior knowledge or conception regarding a concept, even before they study it formally in the school. Sometimes, their conceptions are inconsistent with scientific concept and resulting misconceptions. Some studies found that students encounter misconception of some concepts, particularly in Physics. Three-tier Test is an instrument used to identify student’s misconception and lack of knowledge. A misconception should be differentiate from a lack of knowledge because remediation of a misconception is more difficult than remediation of a lack of knowledge. Besides, both of them may entail different instructional methods. This study focused on diagnosing students’ misconceptions of heat using Three-tier Test. The study is aimed to explain in what concepts the students encounter misconceptions of heat and to explain the prevalence of students’ misconceptions of heat. The method used in this study was a descriptive-exploratory research with non-experimental design. The sample of this study was 150 Grade VII students of five different State Junior High School in Lamongan, East Java. The data was collected through written test using Three-tier Test and administered once. The results showed that students encounter misconceptions in 6 concepts of heat comprising energy, heat, temperature, mass, specific heat capacity, vaporizing, boiling, pressure, boiling point, freezing, and freezing point. Moreover, the results showed that 88% of the students encounter misconception, where the most frequently appeared is misconception about energy and heat that is objects could have a certain quantity of heat in them.Keywords: misconception, heat, three tier testDOI: http://dx.doi.org/10.23960/jpf.v9.n2.202104